What's 'Wisdom' in Local Wisdom Imaginaries on Indigenous Research? - Rangga Kala Mahaswa; Hardiyanti Hardiyanti (Indigenous Southeast Asian and Ethnic Studies, 2025)
The abundance of studies on local wisdom in Indonesia is evident from a Google Scholar search, which yields a wealth of resources. However, the concept of local wisdom and its distinction from related terms such as ‘local knowledge’ and ‘indigenous knowledge’ remains unclear. This article seeks to clarify the notion of ‘wisdom’ by: first, re-examining  the definitions and debates surrounding local wisdom, local knowledge, and indigenous knowledge; second, tracing the models of indigenous research conducted in Indonesia; third, formulating a critical and philosophical approach to interpreting wisdom as conceptualised in Indonesian academic studies; and fourth, critically reflecting on the discourse of local knowledge, highlighting its role not only as a concept but also as a practical social movement that amplifies local voices.